The nova-like nebular optical spectrum of V404 Cygni at the beginning of the 2015 outburst decay. Issue 4 (10th November 2016) - Rahoui, Farid; Tomsick, J. A.; Gandhi, P.; Casella, P.; Fürst, F.; Natalucci, L.; Rossi, A.; Shaw, A. W.; Testa, V.; Walton, D. J.
Abstract: We report on FORS2 optical spectroscopy of the black hole X-ray binary V404 Cygni, performed at the very beginning of its 2015 outburst decay, complemented by quasi-simultaneous Swift X-ray and ultraviolet as well as Rapid Eye Mountain near-infrared observations. Its peculiar spectrum is dominated by a wealth of emission signatures of H i, He i, and higher ionization species, in particular Fe ii . The spectral features are divided between broad redshifted and narrow stationary varieties, the latter being emitted in the outer regions. Continuum and line variability at short time-scale is high, and we find Baldwin effect-like anticorrelations between the full widths at half-maximum and equivalent widths of the broad lines with their local continua. The Balmer decrement H α /H β is also abnormally large at 4.61 ± 0.62. We argue that these properties hint at the broad lines being optically thick and arising within a circumbinary component in which shocks between faster optically thick and slower optically thin regions may occur. We associate it to a nova-like nebula formed by the cooling remnant of strong accretion disc winds that turned off when the mass-accretion rate dropped following the last major flare. The Fe ii lines likely arise from the overlap region between this nebula and the companion star winds, whereas we favour the shocks within the nebula as responsible for the optical continuum via self-absorbed optically thin bremsstrahlung. The presence of a near-infrared excess also points towards the contribution of a strongly variable compact jet or a dusty component.